Chemical Heritage, Volume 29 Number 2 (Chemical Heritage Foundation, 2011)
The image on page 29 of this issue includes a historical image containing antisemitic stereotypes. The image depicts three satyrs destroying teeth with various tools. The satyrs have several stereotypical physical features commonly attributed to Jewish people; beards, large noses, hooves, tails, and horns. Horns and cloven hooves have been used to suggest that Jewish people have an evil nature or are associated with the devil. Additionally, the cloven hooves could be an association with pigs, which are considered “unclean” to Jewish people and are not Kosher for eating. We acknowledge the harm that has been done by including such imagery in this publication and deeply regret its usage.
Keywords: Chemical Heritage Foundation; Medical care; Fluorides; Chandler, Charles Frederick, 1836-1925; Air quality management